Inferências na conversação: uma visão argumentativa. - Barreto, Fanuel Melo Paes (2023)
The investigation presented here addresses the phenomenon of inferences in the context of conversation. Adopting a descriptive and explanatory approach, frankly pluralistic as regards the criterion for selecting the empirical basis, the research has as its main objective to provide a unified treatment of the various inferential processes focused on by the specialized literature in the area of pragmatics, starting from the construction of a model for the interpretation of conversation inspired by the ideas of the philosopher Paul Grice (1913-1988), especially in his conception of verbal language as a variety of rational human behavior and in his view of argumentative rationality as the capacity that people have to justify ideas and actions by means of reasoning. The motivation for such an investigative effort lies, above all, in an understanding of the importance of analyzing verbal communication from a concept of rationality that allows considering the discourse not only in terms of the instrumental adequacy of the strategies employed in its conduction, but also regarding the possibility of justifying, by arguments, the interpretations of the verbal contributions made by the participants in the interaction situations. As a result, one arrives at a characterization of the inferential processes operating in conversational discourse, based on a set of principles that, when compared to Grice's original formulation, proves to be simpler, and that, distinctively, emphasizes the role of argumentative rationality as a decisive ingredient of expectation in the interpretation of utterances. The investigation concludes with a discussion, in purely speculative terms, on the feasibility of extrapolating the results of the treatment of inferences in conversation to other discursive manifestations, in particular, to writing practices.